Pemikiran Behaviorisme dan Implikasinya terhadap Pembelajaran - Berry Devanda; Neviyarni Suhaili; Nora Afnita; Joni Indra Wandi (Institut Agama Islam Sumatera Barat, 2022)
The aim of this study is to identify strategy to use theory of behaviorism in learning. Library research was employed to meet the aim. Several books and articles were analyzed to know what the strategy of teaching in the classroom using behavioristic approach. The results indicate that the purpose of learning is mainly to gain knowledge and forming students’ habits. At the end of the study, critique to the theory and its implication for future research are provided.